1993
DOI: 10.1111/j.1471-0528.1993.tb15210.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal cervical cytology following large loop excision of the transformation zone: a case controlled study

Abstract: Objectives To determine factors that may predict cytological outcome at 6 months following large loop excision of transformation zone (LLETZ) for cervical intra epithelial neoplasia (CIN) and to investigate the outcome in women with continuing cytological abnormality. Design Case controlled retrospective study. Setting Dudley Road Hospital, Birmingham and Midland Hospital for Women. Subjects Fifty‐eight women with abnormal follow up cytology and a control group of 116 women. Main outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 10 publications
0
27
1
Order By: Relevance
“…In a recent survey of colposcopy clinics in the United Kingdom, LLETZ was the most frequently used treatment method, employed in 60% of centres 2 ; 85% of gynaecologists in the United States currently use this procedure 3 . LLETZ is performed easily and quickly as an outpatient procedure, and both the costs and the short term outcome compare favourably with local destructive and other excisional techniques 4–7 . Limited information is available, however, on the longer term results following this treatment modality.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent survey of colposcopy clinics in the United Kingdom, LLETZ was the most frequently used treatment method, employed in 60% of centres 2 ; 85% of gynaecologists in the United States currently use this procedure 3 . LLETZ is performed easily and quickly as an outpatient procedure, and both the costs and the short term outcome compare favourably with local destructive and other excisional techniques 4–7 . Limited information is available, however, on the longer term results following this treatment modality.…”
Section: Introductionmentioning
confidence: 99%
“…Women with larger lesions and margins involved with CIN at LEEP were more likely to have abnormal cervical cytology at follow-up visit (56). We have found that 47% of women with involved surgical margins experience recurrence of CIN (21).…”
Section: Considering Leep Specimen Margins In Follow-up Protocolmentioning
confidence: 94%
“…35,36 The artifacts related to LEEP can be divided into three broad categories, which are outlined in greater detail in Table VIII. In point of fact, it is well-recognized that therapy of any kind not only has localized effects on the target disease, but also affects adjacent nondisease tissues as well.…”
Section: Leep Artifactmentioning
confidence: 99%